PENGARUH FEE AUDIT, DAN MASA PERIKATAN AUDIT TERHADAP KUALITAS AUDIT (SURVEI PADA KANTOR AKUNTAN PUBLIK KOTA BANDUNG) - Afif Prasetyo, Sabirin, (Jurusan Akuntansi, Fakultas Ekonomi dan Bisnis, Universitas Tanjungpura, 2019)
The purpose of this study is to obtain empirical evidence of the influence of audit fees, and audit engagement period both simultaneously and partially on audit quality at public accounting firms in Bandung. The population in this study is the Public Accountant Office in the city of Bandung which is registered at the IAPI Directorate. The technique of determining the sample using census techniques. The number of samples selected in the study was 60 respondents. The analysis technique uses multiple analysis. The results showed that partially Audit Fee had a positive and significant effect on audit quality. While the engagement period does not affect the audit quality. While simultaneously shows that the Audit Fee, and the Engagement Period, significantly influence the Audit Quality Survey at the Bandung Public Accountant Office.Keywords : Audit Fee, Audit Engagement Period, Audit Quality